The Effect of Learning Media Assisted by Doratoon App with Cooperative Model on Students Learning Outcomes - Rum, Junita Angraini Styaning; Odja, Abdul Haris; Supartin, Supartin; Mursalin, Mursalin; Setiawan, Dewa Gede Eka; Mohamad, Wahyu Muzizat (Jurnal Pijar Mipa, 2025)
Learning media assisted by the Doratoon app, combined with engagement, collaboration, and deeper understanding of the material, while the interactive and visual nature of the app helps accommodate various learning styles. This research aims to determine the effect of using learning media assisted by the Doratoon app with a cooperative model on the learning outcomes of work and simple machines in class VIII at SMP Negeri 11 Gorontalo. This study is an experimental research with a one-group pretest-posttest Design. The sampling technique used in this study is Cluster Random Sampling. This research utilizes VIII C, designated as the experimental class, selected randomly through a lottery method. The data for this study were collected through testing techniques. The results of the analysis of the experimental class yield a gain value of 0.83, which indicates that the sample class falls into the high category. Thus, the use of learning media assisted by the Doratoon application with a cooperative model significantly affects student learning outcomes in the material of work and simple machines.